2023
DOI: 10.1021/acsanm.3c00510
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hard/Soft Layer Ordering on Magnetization Reversal of Bimagnetic Nanoparticles: Implications for Biomedical/Theranostic Applications

Abstract: We investigate the spatial distribution of spin orientation in magnetic nanoparticles consisting of hard and soft magnetic layers. The nanoparticles are synthesized in a core–shell spherical morphology where the target stoichiometry of the magnetically hard, high anisotropy layer is CoFe2O4 (CFO), while the synthesis protocol of the lower anisotropy material is known to produce Fe3O4. The nanoparticles have a mean diameter of ∼9.2–9.6 nm and are synthesized as two variants: a conventional hard/soft core–shell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 78 publications
(126 reference statements)
0
1
0
Order By: Relevance
“…The recent ability to fabricate magnetic structures of nanometer size, known as nanomagnetism, has allowed for the study of unique magnetic phenomena that are unobservable at larger length scales [1][2][3][4]. It has been shown that by utilizing nanostructures of varying sizes and shapes, their applicability in fields ranging from biomedicine to memory devices can be improved [2,3,[5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The recent ability to fabricate magnetic structures of nanometer size, known as nanomagnetism, has allowed for the study of unique magnetic phenomena that are unobservable at larger length scales [1][2][3][4]. It has been shown that by utilizing nanostructures of varying sizes and shapes, their applicability in fields ranging from biomedicine to memory devices can be improved [2,3,[5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%